أخلاقيات الأعمال كميزة تنافسية لمنظمات الأعمال دراسة حالة :المطاحن الكبرى للظهرة بمستغانم - فاطمة الزهرة بن نامة; وسيلة العشعاشي تابت أول (My University, 2012)
بعد أن كانت مضاعفة الأرباح الشغل الشاغل لمنظمات الأعمال، أصبحت القضايا الأخلاقية اليوم تشكل أهمية عظمى، فأصبحت التنافسية الأخلاقية من أهم انشغالات المنظمات الاقتصادية، خاصة في واقع الأسواق المحلية والعالمية التي تسعى فيها هذه المنظمات إلى البقاء من خلال اكتساب مزايا تنافسية ذات بعد أخلاقي تجاه مختلف أصحاب المصالح، مما قادها إلى أن تكون أكثر إدراكا واهتماما كي تكون قراراتها أخلاقية وتندرج ضمن إستراتيجيتها التنافسية، فأصبحت المنظمات تسعى إلى التفوق على المنافسين من خلال الاستخدام الصحيح لمعايير المنافسة الأخلاقية. لذا سنتطرق في هذا المقال إلى ماهية أخلاقيات الأعمال ودورها في تحقيق ميزة تنافسية مستدامة للمنظمة وكذا واقع أخلاقيات الأعمال في المنظمة الجزائرية . Abstract: After it was double the profit the main concern of business organizations, have become moral issues today are of great importance, becoming competitive ethics of the major concerns of economic organizations, especially in the reality of local and international markets ; the organizations seek to realize the target basis of survival through the acquisition of competitive advantages that has on ethical trend towards the different stakeholders. That led to the organizations are more aware and interested in to be its decision moral and fall within the competitive strategies, making organizations seek to out perform competitors through the proper use of standards competition moral rather. So we will look at this article to what business ethics and their role in achieving a sustainable competitive advantage for the organization, as well as the reality of business ethics in the Algerian organization.
Keywords: منظمات الأعمال– أخلاقيات الأعمال - الميزة التنافسية - أصحاب المصالح - التنافسية الأخلاقية